Strengthening Regulations on Audit Committees to Prevent State Financial Losses in the Management of the East Java Province APBD - Woro Andrini (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2026)
Regional financial management is crucial? component of the state financial system , which must be conducted transparently , accountably , and in accordance with the principles of good governance . However , in practice , the management of the Regional Revenue and Expenditure Budget (APBD) still faces various problems , such as budget irregularities , weak internal control systems , and low oversight effectiveness . This study aims to analyze the importance of strengthening regulations regarding audit committees to prevent state financial losses in the APBD in East Java Province . The research method used is normative legal research with a statutory and conceptual approach . The results show that the existence of an audit committee as an independent oversight mechanism can improve the quality of internal control and transparency of regional financial management . Therefore , it is necessary to strengthen regulations regarding audit committees in local governments to prevent potential state financial losses and increase accountability in APBD management.